2022
DOI: 10.3389/fimmu.2022.1008084
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RNAs are processed into 22-nt vsRNAs in Vero cells

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the global pandemic, resulting in great fatalities around the world. Although the antiviral roles of RNA interference (RNAi) have been well studied in plants, nematodes and insects, the antiviral roles of RNAi in mammalians are still debating as RNAi effect is suspected to be suppressed by interferon (IFN) signaling pathways in most cell types. To determine the role of RNAi in mammalian resistance to SARS-CoV-2, we studied the profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…We next examined the impact of NSP2 on the repression activity of miRNAs on a reporter mRNA that contains miRNA binding sites. A recent analysis of dysregulated host miRNAs revealed miR-20a as one of the most significantly upregulated miRNAs in SARS-CoV-2 infected cells [23], likely due to its immunosuppressive effects [24,25]. We used a dual luciferase reporter system in which the Firefly Luciferase (FL) mRNA contains 3x miR-20abinding sites within its 3´ UTR (miR-20 WT; Fig.…”
Section: Results: Nsp2 Interacts With the Components Of Mirisc And En...mentioning
confidence: 99%
See 2 more Smart Citations
“…We next examined the impact of NSP2 on the repression activity of miRNAs on a reporter mRNA that contains miRNA binding sites. A recent analysis of dysregulated host miRNAs revealed miR-20a as one of the most significantly upregulated miRNAs in SARS-CoV-2 infected cells [23], likely due to its immunosuppressive effects [24,25]. We used a dual luciferase reporter system in which the Firefly Luciferase (FL) mRNA contains 3x miR-20abinding sites within its 3´ UTR (miR-20 WT; Fig.…”
Section: Results: Nsp2 Interacts With the Components Of Mirisc And En...mentioning
confidence: 99%
“…However, in principle NSP2 could also enhance the silencing mediated by antiviral miRNAs [39]. To avoid the potential harmful effects of NSP2-induced repression by antiviral miRNAs, the virus can manipulate the expression pattern of antiviral miRNAs [23,[40][41][42][43]. Analysis of the expression of 128 human miRNAs with potential to target the SARS-CoV-2 genome revealed their very low expression in lung epithelia [43], which likely allows the virus to avoid the effects of antiviral miRNAs and replicate in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We next examined the impact of NSP2 on the repression activity of miRNAs on a reporter mRNA that contains miRNA-binding sites. A recent analysis of dysregulated host miRNAs revealed miR-20a as one of the most significantly upregulated miRNAs in SARS-CoV-2-infected cells ( Liu et al, 2022 ), likely due to its immunosuppressive effects ( Cox et al, 2010 ; Reddycherla et al, 2015 ). We used a dual luciferase reporter system in which the firefly luciferase ( FL ) mRNA contains 3× miR-20a -binding sites within its 3′ UTR (miR-20 WT; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hitherto, our data have revealed that NSP2 augments miR-20a -mediated repression. To investigate whether NSP2 also augments the translational repression by other miRNAs, we used two other abundant miRNAs: let-7a , which is also upregulated in SARS-CoV-2-infected cells ( Nersisyan et al, 2020 ), and miR-92 , the expression of which is not known to be modulated by SARS-CoV-2 ( Liu et al, 2022 ). Similar to the miR-20 reporter ( Fig.…”
Section: Resultsmentioning
confidence: 99%